Advertisement Call Variation of Two Frog Species along an Urban–Rural Gradient in Shanghai, China - Ningning Liu; Shurong Zhong; Tianhou Wang; Xiuzhen Li; Li Wei; Chunjing Zou; Shanshan Zhao; Ben Li (Diversity, 2022)
Urbanization has a significant influence on amphibian communities, populations, and individuals because of habitat loss, degradation of habitat quality, and habitat fragmentation. Advertisement calls of anurans are used for communication and play an important role in reproduction; however, how anthropogenic noise and habitat change caused by urbanization affect anuran advertisement calls is less well known. In this study, we examined changes in the advertisement calls of two frog species, the ornamented pygmy frog (Microhyla fissipes) and rice frog (Fejervarya multistriata), during the breeding season along an urban–rural gradient in Shanghai, China. We used the percentage of impervious area (including buildings and roads) in each 2 km-radius landscape to represent the urbanization index of 34 study sites. We then measured five advertisement call parameters (call duration, call interval, call rate, pulse rate, and dominant frequency) of these two species (100 males of F. multistriata and 89 males of M. fissipes) in each study site from May to July in 2020 and 2021. We explored how the urbanization index and other variables (air temperature, snout–vent length and calling situation (one frog species calling, or two frog species calling together)) in each study site affected these call parameters. The results showed that the dominant frequency of M. fissipes was significantly negatively related to urbanization index, and call duration and call interval were significantly negatively related to air temperature; furthermore, call rate and pulse rate were significantly positively related to air temperature, and call duration was also significantly positively related to snout–vent length. For F. multistriata, pulse rate was significantly negatively related to urbanization index, snout–vent length, and situation (two frog species calling together), but significantly positively related to air temperature; by contrast, call interval was significantly positively related to snout–vent length. We suggested that these two frog species had different responses to urbanization, which could help us to better understand the change of anuran breeding behaviors and reproductive life-history strategies in the face of rapid urbanization.